Energy harvesting sensitivity analysis and assessment of the potential power and full car dynamics for different road modes. (15th September 2018) - Abdelkareem, Mohamed A.A.; Xu, Lin; Guo, Xuexun; Ali, Mohamed Kamal Ahmed; Elagouz, Ahmed; Hassan, Mohamed A.; Essa, F.A.; Zou, Junyi
Graphical abstract: Highlights: The damping power dissipation can be one of the design considerations besides the vehicle dynamics. The potential power correlates strongly to speed, road, and tire characteristics. For roll mode input, the midsize passenger car is dissipating damping power as much as 0.9 kW. The overloaded and heavy vehicles are dissipating an energy up to 3 kW per damper. The overall potential power of a passenger car reaches 1 kW for HWFET cycle. Abstract: Automobiles are dissipating a considerable amount of vibration energy that is worth of being harvested where it can be exploited in different applications. For a full vehicle suspension assembly, the conflict between the potentially harvested energy and vehicle dynamics represented by ride quality and road safety and handling was comprehensively illustrated for different input modes. The discrepancy between the bounce input mode and the roll input mode was also sufficiently clarified based on an extensive parametric analysis covering the design parameters and the operational parameters as well. Comprehensive simulations were then conducted to estimate the amount of wasted energy in vehicle suspension system for different types of cars (passenger, bus, truck, and off-road vehicle), besides the potential harvested power was quantified for different standard driving cycles (NEDC, WLTP, HWFET, and FTP). Based on that, a 7-DOF full car suspension model was implemented in Matlab/Simulink environment and induced by different levels of road irregularities. The findings of this paper showed that the vibration intensity levels changed clearly in the complex input mode that reflects a realistic view of the real vehicle dynamics on the roads compared to the ideal results from the bounce input mode. Our results also indicate that a potential power up to 420 W can be collected considering standard driving patterns and roll mode input. The analysis indicates that the overloaded vehicles are suitable for the energy harvesting system based on the harvestable energy per unit cost.